Analisis Framing Media Online dalam Pemberitaan Menteri Sosial Republik Indonesia, Tri Rismaharini - Listya Anindita; Leo Randika; Riska Y. Imilda; Yanti Widayanti; Dedeh Fardiah (Unitri Press, 2022)
Mass media has become the main source of information for the public to find out the latest and actual news. Through the mass media, various forms of freedom are shown to voice various statements and opinions. This is where the media plays a strong role in bringing up interesting issues for the audience, including in the process of framing a news story. There is no doubt that the framing of the news relates to public figures who are often the targets. This research focuses on the online media Kompas.com when framing news about the Minister of Social Affairs (Mensos) Tri Rismaharini in the December 2021 period. Of course, it aims to see how far Kompas.com is framing the news and packaging news about Tri Rismaharani for public consumption. This research is also supported by using qualitative research methods, constructivist paradigms, and framing analysis. This result of framing analysis on this study indicate how the media constructs and conveys news by format and narrative. In the same event, when viewed from the packaging from one news to another, this frame depends on the interests of a media so that it shows the media's construction of a reality. This news is then formed with a frame through the selection of emphasis on an issue. Abstrak Media massa telah menjadi sumber informasi utama bagi masyarakat untuk mengetahui berita terbaru dan teraktual. Melalui media massa berbagai wujud kebebasan ditampilkan untuk menyuarakan berbagai pernyataan dan pendapat. Di sinilah media berperan kuat untuk memunculkan isu-isu menarik bagi khalayak termasuk dalam proses framing sebuah berita. Tak ayal framing pemberitaan berkenaan dengan tokoh publik yang kerap kali menjadi sasaran. Penelitian ini salah satunya, fokus pada media online Kompas.com saat membingkai pemberitaan mengenai Menteri Sosial (Mensos) Tri Rismaharini di periode Desember 2021. Tentu penelitian ini bertujuan untuk melihat sejauh mana Kompas.com membingkai dan mengemas pemberitaan tentang Tri Rismaharani untuk konsumsi publik. Penelitian ini didukung dengan menggunakan metode penelitian kualitatif, paradigma konstruktivis, serta analisis framing. Hasil analisis framing pada penelitian ini menunjukkan bagaimana media mengkonstruksi dan menyampaikan berita dengan format dan narasinya. Dalam suatu peristiwa yang sama, bila dilihat dari pengemasan dari berita satu ke berita lainnya frame ini tergantung pada kepentingan suatu media sehingga memperlihatkan konstruksi media atas suatu realitas. Berita ini lalu dibentuk dengan frame melalui seleksi penekanan terhadap sebuah isu.